Implementation of Women Representatives in Regional Legislative Election in Salatiga 2019 (Study of the Gerindra Party and the Nasdem Party) - Ambar Ayuningsih (JIL : Journal of Indonesian Law, 2020)
Political parties, as a democratic institution, have a strategic role in empowering women in politics. One of the crucial roles of the party is to guide women party cadres to be prepared to become qualified women cadres and, at the same time to boost women representation in politics, especially in the legislative body. Women representation in politics is needed because society needs to have balanced views between the needs of men and women. Besides, the formulated public policy must also represent the interests of both. This type of research is qualitative research as a socio-legal research by expressing symptoms thoroughly and by the context through collecting data from the field and interacting directly with the two parties in the City of Salatiga, namely the Gerindra Party and the Nasdem Party, as well as candidates women from both parties. The policy adopted by the Gerindra Party and the Nasdem Party by applying the open and closed recruitment method has resulted in the fulfillment of a 30% quota for women’s representation so that the implication of the Gerindra and Nasdem Party legislative candidates has been determined as a permanent candidate in the 2019 concurrent elections.